Measuring Supply Chain Performance and Developing Competitive Strategy on Small Medium Enterprise Craft Industry using SCOR-AHP Model - Purnama, Dwi Adi; Novianto, Didin Dwi; Haryanti, Nur Laily (TALENTA Publisher, 2025)
Small and medium enterprises (SMEs) require support to evolve into established organizations due to their strong flexibility to change. Nonetheless, numerous obstacles confront SMEs in their efforts to develop and compete. This study seeks to evaluate supply chain performance and the formulation of competitive strategies inside small and medium-sized enterprises (SMEs). This serves as an option for assessing supply chain performance while emphasizing the formulation of competitive strategies to enhance it, encompassing the management of material, information, and financial flows from both supply and demand perspectives. The evaluation of supply chain performance is conducted with the SCOR model, which relies on the identification of Key Performance Indicators (KPIs) derived from the outcomes of the SMEs business mapping process. Subsequently, multi-criteria decision making (MCDM) employing the Analytical Hierarchy Process (AHP) is utilized to assign weights to the KPI criteria for assessing supply chain performance and guiding competitive strategy creation. The study's results identified the indicators categorized into planning, production, sourcing, delivery, and returns. The measurement of supply chain performance suggests that the case study industry has a value of 84.11, signifying commendable performance. Moreover, competitive strategies, using Kraljic Matrix, Six Sigma, Lean Method, or mixed strategies, have been suggested to enhance supply chain performance and business competition, informed by the outcomes of the SCOR model and the MCDM approach.